Processing of mRNA from human leukocytes by biomagnetical separation: comparison with current methods of RNA isolation - Mrázek, František; Petřek, Martin (Acta Universitatis Palackianae Olomucensis Facultatis medicae. Biomedical papers, 1999)
The article refers to the technique of biomagnetical separation (BS) of mRNA using "Dynabeads mRNA DIRECT". After a brief survey of RNA isolation methods authors describe a general procedure of BS as well as its concrete application for mRNA isolation from bronchoalveolar cells. Authors report results of specific experiments to assess the efficiency and accuracy of mRNA isolation by BS. The applicability of BS technique for the gene expression studies is discussed in the end of the article.
Keywords: magnetismus; RNA, Messenger; Bronchoalveolar Lavage Fluid; Humans; Magnetics; messenger RNA; lidé; Leukocytes; bronchoalveolární lavážní tekutina; leukocyty